Emergency Radiology Imaging and Intervention - Marincek, Borut; Dondelinger, Robert F.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
Why write a book on emergency radiology? In many coun- decline. There is an increasing trend towards the use of tries, hospital emergency departments have become a MDCT to evaluate traumatic injuries and non-traumatic major part of the healthcare safety net. In the last decade emergencies. The use of workstations for reporting and for economically-driven structural changes in health care further image reconstruction becomes standard practice. delivery have caused a dramatic increase in emergency On the occasion of the European Congress of Radiology department visits. In response to capacity and staffing (ECR) 2003 and 2004 a Categorical Course on “Emergency pressures, hospitals are developing and implementing a Radiology”has been organized to assess current devel- variety of strategies designed to improve patient flow and ments and concepts in this rapidly growing field. reduce overcrowding in the emergency department. Numerous radiologists,all outstanding and international- Several factors are considered critical for success, such as ly renowned experts in their field,have made superb c- having the right multidisciplinary teams in place and opti- tributions in an ECR syllabus. These authors have now mizing the use of imaging tests. For a critical care physi- made a second effort and updated their contributions for cian it is paramount to obtain the images quickly and for this book. The chapters in the book mirror the topics p- them to be interpreted accurately. sented in the ECR course, encompassing imaging ap- To accomplish this, the emergency radiology division proaches as well as interventional aspects.
Emergency Radiology: Role of Imaging -- Role of Imaging in the Management of Trauma Victims -- Role of 3D Imaging in the Emergency Room -- Traumatic Injuries: Imaging and Intervention -- Hemostatic Arterial Embolization in Trauma Victims at Admission -- Imaging and Intervention in Post-traumatic Complications (Delayed Intervention) -- Imaging of Head Injuries -- Imaging of Facial Injuries -- Imaging of Spinal Injuries -- Imaging of Thoracic Injuries -- Vascular Injuries of the Thorax: Multi-Detector-Row CT and 3D Imaging -- Imaging of Abdominal and Pelvic Injuries -- Imaging and Intervention of Large Arterial Trauma -- Pelvic Fractures -- Traumatic Injuries: Imaging of Peripheral Muskuloskeletal Injuries -- Non-Traumatic Neurologic Emergencies: Imaging and Intervention -- Imaging of Cerebral Ischemia -- Neuroradiological Emergency Interventions -- Non-Traumatic Thoracic Emergencies: Imaging and Intervention -- Acute Chest Pain: Diagnostic Strategies -- CT Diagnosis of Acute Pulmonary Embolism -- CT Venography in an Integrated Diagnostic Strategy of Acute Pulmonary Embolism and Venous Thrombosis -- Imaging and Treatment of Thoracic Fluid and Gas Collections -- Non-Traumatic Abdominal Emergencies: Imaging and Intervention -- Acute Abdominal Pain: Diagnostic Strategies -- Imaging of Acute Intestinal Obstruction -- Imaging and Intervention in Gastrointestinal Hemorrhage and Ischemia -- Imaging and Intervention in Sepsis -- Non-traumatic Abdominal Emergencies: Imaging and Intervention in Acute Biliary Conditions -- Imaging and Intervention in Acute Pancreatic Conditions -- Non-traumatic Uroradiological Emergencies -- Non-Traumatic Vascular Emergencies: Imaging and Intervention -- Imaging and Intervention in Acute Non-traumatic Arterial Condition -- Imaging and Intervention in Acute Venous Occlusion -- Management of Occluded Hemodialysis Shunts, Grafts, and Venous Access -- Imaging Pediatric Emergencies -- Pediatric Neurological Emergencies -- Thoracic Emergencies -- Pediatric Emergencies: Non-traumatic Abdominal Emergencies.
Keywords: Radiology; Internal medicine; Neurology .; Traumatology; Imaging / Radiology; Diagnostic Radiology; Internal Medicine; Neurology; Traumatic Surgery